Employability Skills and Career Readiness Among Muslim Vocational Students: Mediating Role of Career Decision-Making Self-Efficacy - Wenny Wulandari; Arif Sahin; Wise Rahmawan; Farouq Fathurrahman; Muh. Azhar Mubarak; Wiffy Zalina Putri (State Islamic University (UIN) Salatiga, 2026)
Rapid changes in the labour market require vocational students to develop career readiness supported by employability skills and psychological resources for career decision-making. This study tested the direct and indirect effects of employability skills on career readiness via Career Decision-Making Self-Efficacy (CDMSE) among Grade-12 Muslim vocational students. Using a cross-sectional design, all students at SMK Multicomp Depok, Indonesia (N = 215) were surveyed using saturated sampling, with Muslim status verified through school records. Adapted measures were used: the Self-Perceived Employability Scale (α = .96), the Career Decision-Making Self-Efficacy Scale (α = .95), and the Student Career Readiness Scale (α = .98). Mediation was examined using PROCESS Macro for SPSS (Model 4) with bootstrap resampling. Employability skills significantly predicted CDMSE (b = 1.21, SE = .12, t = 10.22, p < .01; R² = .33) and career readiness (direct effect controlling for CDMSE: b = .66, SE = .11, t = 6.09, p < .01). CDMSE also significantly predicted career readiness (b = .42, SE = .05, t = 8.13, p < .01; model R² = .53). The indirect effect of employability skills on career readiness via CDMSE was significant (b = .51, SE = .09, 95% BC CI [.35, .70]), indicating partial mediation. The findings support Social Cognitive Career Theory and suggest that guidance and counseling programs should integrate employability development with interventions that strengthen decision-making self-efficacy. Limitations include the cross-sectional design, self-report measures, and a single-school sample; future research should use longitudinal designs and broader settings to improve generalizability.